Haar spectrum of Bent Boolean functions - Siddiqi, Mohammad Umar; Rafiq, Hashum M. (Institute for Mathematical Research, Universiti Putra Malaysia, 2016)
Bent Boolean functions play a very significant role in the design of strong symmetric cryptosystems. In this paper, we present an analysis of Bent functions in the Haar domain. We first present a brief overview of Bent Boolean functions and then derive expressions for the Haar spectrum of Bent functions. The Haar spectral coefficients of Bent functions are given in two ways namely; in terms of sub-intervals over the entire spectrum,as well as, individual spectral coefficients. Finally, we conclude the paper with a summary of findings and suggestions for further work for utilizing the results for design of secure cryptosystems.